ANALYSIS OF RHETORICAL AND FIGURATIVE LANGUAGE STYLES IN GEGURITAN COLLECTION DJAKA LODANG MAGAZINE FEBRUARY-MAY 2014 EDITION - Dianawati, Dianawati; Bagiya, Bagiya; Rochimansyah, Rochimansyah (Department Javanese Literature and Language Education in Collaboration with Faculty of Teacher Training and Education Muhammadiyah University of Purworejo, 2025)
This study aims to describe the rhetorical and figurative language styles in geguritan (traditional poetry forms in Javanese) collection of Djaka Lodang magazine in February-May 2014 edition. This type of research is qualitative research. Data collection used documentation technique. Data analysis used descriptive method. The result of the research shows that the language style in the collection of geguritan of Djaka Lodang magazine in February-May 2014 edition consists of rhetorical language style from 69 geguritan including: alliteration, assonance, anastrophe, apostrophe, asindenton, polysindenton, periphrasis, chiasmus, ellipsis, euphemism, hysteron proteron, pleonasm and tautology, erotesis, silepsis, correction, and hyperbole. The figurative language styles of the 69 geguritan include: simile, metaphor, personification, epithet, synecdoke, metonymy, antonomasia, irony, cynicism, sarcasm, and paranomasia. The collection of geguritan in the February-May 2014 edition of Djaka Lodang magazine illustrates that stylistic elements in a poem can add an aesthetic touch and enrich the meaning.